Novel Co-rich high performance twinning-induced plasticity (TWIP) and transformation-induced plasticity (TRIP) high-entropy alloys - Wei, Daixiu; Li, Xiaoqing; Jiang, Jing; Heng, Weicheng; Koizumi, Yuichiro; Choi, Won-Mi; Lee, Byeong-Joo; Kim, Hyoung Seop; Kato, Hidemi; Chiba, Akihiko (Scripta materialia, 2019)
The equiatomic CoCrMnNiFe high-entropy alloy (HEA) has attracted much attention owing to its exceptional mechanical properties. Here, we designed novel face-centered cubic (fcc) phase Co-rich non-equiatomic CoCrMnNiFe HEAs with tensile properties superior to the counterparts, derived from lowering stacking fault energy (SFE) via modifying constituent concentrations. The decrease of Mn, Ni, Fe meanwhile increase of Co, Cr concentrations does reduce the SFE value, based on ab initio and thermodynamics calculations. Hereinto, Co35Cr20Mn15Ni15Fe15 and Co35Cr25Mn15Ni15Fe10 HEAs overcame the strength-ductility trade-off, contributing to twinning-induced plasticity (TWIP) or transformation-induced plasticity (TRIP) effects, respectively. The present study sheds light on developing high performance HEAs. [Display omitted]